Education and society in late imperial China, 1600-1900 - Elman, Benjamin A., 1946-; Woodside, Alexander (Studies on China, 1994)
With unprecedented breadth, this volume integrates the history of late imperial China with the history of education over three centuries of Chinese social, political, and intellectual life. The essays probe beneath the educational ideals enunciated by Neo-Confucian philosophers to elucidate actual educational practice in China from the late Ming dynasty to the late Ch'ing. Among the questions addressed: How was education affected by gender and kinship relations?